2018
DOI: 10.1002/cpt.1167
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Consistency of Drug Interaction Information in Drug Labels Among the United States, the United Kingdom, China, Japan, and Korea

Abstract: Information gap in drug labeling among countries create challenges in therapeutic use of drugs. We aimed to evaluate the consistency of drug interaction information in drug labels among five countries. The study drugs were chosen from the commonly approved drug list in the US, UK, China, Japan, and Korea. The degree of agreement of drug interaction data was evaluated by kappa coefficient. Thirty-eight drugs were evaluated, and moderate degree of agreement was observed among all countries' labeling (κ = 0.43, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Information about DDIs are presented in the relevant sections of the product label, the purpose of which is to assist the prescriber in the use of a specific medicine. However, a recent assessment of the consistency of DDI information in drug labels in several countries (USA, UK, China, Japan, Korea) showed only a moderate level of agreement among the countries' labelling . The study concluded that there is a need for international harmonization of the drug labelling process and regulation to produce standardized information that can ensure safe drug therapy worldwide.…”
Section: Discussionmentioning
confidence: 91%
“…Information about DDIs are presented in the relevant sections of the product label, the purpose of which is to assist the prescriber in the use of a specific medicine. However, a recent assessment of the consistency of DDI information in drug labels in several countries (USA, UK, China, Japan, Korea) showed only a moderate level of agreement among the countries' labelling . The study concluded that there is a need for international harmonization of the drug labelling process and regulation to produce standardized information that can ensure safe drug therapy worldwide.…”
Section: Discussionmentioning
confidence: 91%
“…These findings align with previously demonstrated divergence in product monographs from North American, European, and Asian regulatory authorities. 7-12…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
“…These findings align with previously demonstrated divergence in product monographs from North American, European, and Asian regulatory authorities. [7][8][9][10][11][12] Recommendations for the treatment of the uncomplicated patient with atrial fibrillation or acute venous thromboembolism (VTE), with normal renal and hepatic function and few concomitant medications, were similar across the regulatory authorities. However, important differences emerged when the patient is no longer "uncomplicated"in situations when clinicians are likely to seek clarification for prescribing information.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…14) A separate study compared the indications of reference labels among the US, Japan, and the European Union. 15) Another study compared package inserts among the US, the United Kingdom, China, South Korea, and Japan concerning information described in the drug-drug interaction section, 16) whereas one study compared pharmacokinetics information among China, Japan, and the US regarding anticancer drugs. 17) A study on the operational aspects of the Japanese package insert 18) and a proposal for improving the package insert based on previous studies 19) have also been reported.…”
Section: Introductionmentioning
confidence: 99%